2022
DOI: 10.21203/rs.3.rs-2259712/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ribosomal protein P0A is required for embryo development in rice

Abstract: The P-stalk is a conserved and vital structural element of ribosome. The eukaryotic P-stalk exists as a P0-(P1-P2)2 pentameric complex, in which P0 function as a base structure for incorporating the stalk onto 60S pre-ribosome. There is only a single copy of P0 gene in yeast and most animal species. Prior studies have suggested that P0 genes are indispensable for survival in yeast and animals. In contrast, each plant species has at least two copies of P0 genes, however, the functions of P0 genes in plants rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Studies (Chen, M.C., et al, 2012) have confirmed that Ba duan Jin can improve the quality of sleep in the elderly. This is associated with promoting melatonin secretion, reducing the active level of the hypothalamic-pituitary-adrenergic axis, and inhibiting hyperarousal (Hou Jiangtao, et al, 2022). Especially for patients with anxiety and insomnia, there is a double therapeutic effect, and studies (Wang Fang, et al, 2022) have shown that after 3 months of Ba duan jin intervention, patients have anxiety relief and sleep quality is improved.…”
Section: Ba Duan Jin Action Analysismentioning
confidence: 99%
“…Studies (Chen, M.C., et al, 2012) have confirmed that Ba duan Jin can improve the quality of sleep in the elderly. This is associated with promoting melatonin secretion, reducing the active level of the hypothalamic-pituitary-adrenergic axis, and inhibiting hyperarousal (Hou Jiangtao, et al, 2022). Especially for patients with anxiety and insomnia, there is a double therapeutic effect, and studies (Wang Fang, et al, 2022) have shown that after 3 months of Ba duan jin intervention, patients have anxiety relief and sleep quality is improved.…”
Section: Ba Duan Jin Action Analysismentioning
confidence: 99%